Compondo a aquarela da vida de meninos e meninas de rua no município de Vitória - Almeida, Fernanda Silva de (2011)
The present study aims to examine the lives of children and adolescents living on the streets in the municipality of Vitória-ES. The survey was designed from a work experience as a Psychologist Team Approach Social Project Street of the City of Victoria whose main objective is to develop systemic work of monitoring public parks, squares and public spaces of the city, identifying and addressing children and adolescents on the streets. The purpose of the paper's approach is to provide for the elimination of the streets from individual and family psychosocial intervention. In the course of this work, there has been a series of questions regarding the place occupied by these children and adolescents in the city, and the place occupied by the city in their life. The methodological approach used based on principles of cartography in order to give emphasis to the monitoring of research processes rather than a methodological technicality. e used oral history as a resource that enabled the clarification of individual trajectories of these children and adolescents, reconstructing history through its many versions, capturing the logic of the relationship through the street-boy meaning expressed in the language of the actor. There was an analysis of narratives constructed from the oral testimony of four subjects studied from the theoretical perspective of Institutional Analysis, using authors such as Foucault, Deleuze and Guattari in the attempt to naturalize the social places occupied by children and adolescents on the streets , for example, the "dysfunctional family", the "dangerous", the "unrecoverable", etc. It is concluded from this work, for assistance can have an effective follow-up of boys and girls on the street in order to help them overcome this situation, we must go beyond a psychological or social, the which is established in the Statute of Children and Adolescents and the National Plan for Social Assistance. You have to get dirty, get closer to the existential reality of these subjects, see them beyond the label of "street children" and believe that they can be other things too. View the lives of these children and adolescents is composed of various colors and what they can and need to blend, because each one has its importance in the composition of life of these watercolors of "street children".